Use of special knowledge in the investigation of crimes in the field of credit - Volodymyr Bondar; Anton Korshun; Maryna Bochkarova; Yevhen Priakhin; Andrii Nahornyi; Tetiana Chashnytska (Jurnal Cita Hukum, 2024)
On the basis of the results of the analysis of judicial and expert practice, as well as scientific sources, a study of the problematic aspects of the involvement of a specialist in the conduct of individual investigative (search) actions, the appointment and conduct of expert studies in the investigation of crimes in the field of lending was carried out. It has been established that the existence of schemes of criminal activity is typical for the technology of criminal enrichment through credit and financial transactions, which include: appropriation of bank credit resources, fraudulent obtaining of credit, fraud with financial resources. It was emphasized that the clarification of certain circumstances in the mentioned criminal proceedings is impossible without the use of special knowledge, primarily related to making changes to the relevant official documents. Typical investigative (search) actions are highlighted, in which it is necessary to actively use the help of a specialist, as well as the main areas of application of special knowledge by the parties to criminal proceedings, in particular, the investigator and the defense attorney. The importance of forensic examination (technical examination of documents, handwriting examination, complex forensic dactyloscopy, handwriting and technical examination of documents) is indicated as one of the main means of obtaining evidence during the investigation of criminal offenses in the field of lending. Particular attention is focused on determining the purpose, subject and tasks of technical examination of documents in the investigation of criminal offenses of this category.